SARS-CoV-2 tetrameric RBD protein blocks viral infection and induces potent neutralizing antibody response - Liu, Zheng; Yang, Chenglu; Zhang, Haokun; Cao, Guojie; Wang, Senzhen; Yin, Siwen; Wang, Yanming (Frontiers in Immunology, 2022)
The pandemic of coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has posed serious threats to global health and economy and calls for the development of safe treatments and effective vaccines. The receptor-binding domain in the spike protein (SRBD) of SARS-CoV-2 is responsible for its binding to angiotensin-converting enzyme 2 (ACE2) receptor. It contains multiple dominant neutralizing epitopes and serves as an important antigen for the development of COVID-19 vaccines. Here, we showed that dimeric SRBD-Fc and tetrameric 2xSRBD-Fc fusion proteins bind ACE2 with different affinity and block SARS-CoV-2 pseudoviral infection. Immunization of mice with SRBD-Fc fusion proteins elicited high titer of RBD-specific antibodies with robust neutralizing activity against pseudoviral infections. As such, our study indicates that the polymeric SRBD-Fc fusion protein can serve as a treatment agent as well as a vaccine for fighting COVID-19.